Schuyler Colfax correspondence and speeches - Colfax, Schuyler, 1823-1885.
Correspondence and speeches documenting Colfax's ownership and editorship of the St. Joseph Valley Register, a Whig newspaper in South Bend, Ind.; his involvement in Whig and Republican party politics; and his tenure as U.S. representative from Indiana and as U.S. vice president. Subjects include state and national politics, operation of the newspaper, events in Washington, D.C., and William T. Sherman. Correspondents include Henry B. Anthony, Roscoe Conkling, Jay Cooke, Henry L. Dawes, John Sherman, and Alfred Wheeler.
Microfilm edition available for a portion of the collection
Microfilm produced from originals in the Manuscript Division.
U.S. vice president and U.S. representative and newspaper editor of Indiana.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Keywords: Anthony, Henry B. -- 1815-1884 -- Correspondence; Conkling, Roscoe, -- 1829-1888 -- Correspondence; Cooke, Jay, -- 1821-1905 -- Correspondence; Dawes, Henry L. -- 1816-1903 -- Correspondence; Sherman, John, -- 1823-1900 -- Correspondence; Sherman, William T. -- 1820-1891.; Wheeler, Alfred -- Correspondence; Republican Party (U.S. : 1854- ); Whig Party (U.S.); St. Joseph Valley register; American newspapers -- Indiana -- South Bend; Indiana -- Politics and government -- 19th century; United States -- Politics and government -- 19th century; Washington (D.C.) -- History; Newspaper editors; Representatives, U.S. Congress -- Indiana; Vice-Presidents -- United States